Electron and ionic transport in high-radioactive silicate alkali-earth glasses - Zhydkov, O. (Condensed Matter Physics, 2004)
The paper is devoted to the experimental study of electric transport in a very special substance, namely alkali-earth glasses containing the noticeable quantity (up to 10%) of dissolved irradiated uranium nuclear fuel and its fission and daughter products as well. Such a high-radioactive product was formed at the active stage of the well-known heavy nuclear accident which occurred on Chornobyl NPP facility in 1986. The soft matter behaviour was established by measuring the temperature dependence of viscosity, where the glassy properties had been identified unambiguously. Static electric conductivity temperature dependence was measured for 80 K–1000 K temperature interval. The transport processes connected with thermal activation of electrons, hopping conductivity in the band tails and variable range hopping (VRH) were identified. The band structure of such glasses manifests the energy gap of 1.8–2.0 eV width, which formed due to long-range order and wide band tails connected with horizontal disorder, which, in its turn, may originate from numerous traps and internal radiation damages. The latter makes it possible to identify the investigated matter as devitrified glass. The distinguishing feature of such devitrified glasses is low ionization energy for electrons, providing a high spatial density of electron excitations in α -particle tracks, which leads to such a collective phenomena as the so-called Coulomb explosion.